Probing interfaces of pea protein-stabilized emulsions with a fluorescent molecular rotor - Velandia, Santiago F.; Bittermann, Marius R.; Mirzahossein, Elham; Giubertoni, Giulia; Caporaletti, Federico; Sadtler, Véronique; Marchal, Philippe; Roques-Carmes, Thibault; Meinders, Marcel B. J.; Bonn, Daniel (Frontiers in Soft Matter, 2023)
Pea protein isolate (Pisum sativum L., PPI) has been much studied in the last decade because of its potential as a bio-based alternative for surfactants to produce innovative and environmentally friendly emulsion products. PPI is ideal due to its favorable nutritional properties, low allergenicity and low environmental impact. Despite its growing popularity, understanding the stabilisation mechanism of emulsions stabilized with PPI remains a key question that requires further investigation. Here, we use fluorescence lifetime microscopy with molecular rotors as local probes for interfacial viscosity of PPI stabilized emulsions. The fluorescence lifetime correlates to the local viscosity at the oil-water interface allowing us to probe the proteins at the interfacial region. We find that the measured interfacial viscosity is strongly pH-dependent, an observation that can be directly related to PPI aggregation and PPI reconformation. By means of molecular rotor measurements we can link the local viscosity of the PPI particles at the interface to the Pickering-like stabilisation mechanism. Finally, this can be compared to the local viscosity of PPI solutions at different pH conditions, showing the importance of the PPI treatment prior to emulsification.